Needs Analysis for Developing ILFS (Indonesian Language for Foreign Speakers) Materials with Multicultural Education using A Communicative Approach for Thai Students - Ekawati, Tatik; Sayuti, Suminto A.; Syamsi, Kastam (Journal of Cultural Analysis and Social Change, 2026)
The study follows a mixed-methods research approach as it incorporates both quantitative surveys and qualitative descriptions in assessing needs for the development of ILFS teaching materials that integrate multicultural education with a communicative approach for Thai university students. A total of 85 students and 6 ILFS instructors participated in this study from the following universities: Thammasat University, Chiang Mai University, Naresuan University, Walailak University, Fatoni University, Prince of Songkhla University (Pattani Campus), and Rajabhat Songkhla University. Accordingly, the data collection tool consisted of a four-point Likert scale questionnaire, structured interviews, and document analysis. The questionnaire measured students' perceptions concerning the relevance of multicultural content, the communicative approach taken, and contextual suitability of the teaching materials. The interviews investigated students' expectations and learning needs. The needs analysis, therefore, presents the first step of Borg and Gall's 2007 research and development model. It stresses that user data should be collected before the design of instructional materials. Thus, from these results, one would note that the existing ILFS teaching materials do not represent the local cultural context in which Thai students learn. Hence, it points to the need for the incorporation of multicultural values and a communicative approach within the ILFS learning materials. The results would then form the basis upon which to design contextual, relevant, and needs-driven beginner-level ILFS materials for Thai university students.